2021
DOI: 10.3390/microorganisms9040858
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Coffee Production and the Future Microbiome and Mycotoxin Profile Considering the Climate Change Scenario

Abstract: Brazil holds a series of favorable climatic conditions for agricultural production including the hours and intensity of sunlight, the availability of agricultural land and water resources, as well as diverse climates, soils and biomes. Amidst such diversity, Brazilian coffee producers have obtained various standards of qualities and aromas, between the arabica and robusta species, which each present a wide variety of lineages. However, temperatures in coffee producing municipalities in Brazil have increased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 88 publications
(118 reference statements)
0
14
0
Order By: Relevance
“…Several surveys of the literature also show that a few studies have been conducted on saprotrophic fungi associated with coffee [ 11 ]. Most of the studies focus on pathogens, as pathogenic fungal infections reduce coffee yield and quality, and thus affect farmers’ income and consumers’ health [ 12 , 13 ]. Some research has shown that saprotrophic fungus Phialomyces macrosporus isolated from leaf litter has the potential to be used in the management of coffee halo blight in seedlings [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several surveys of the literature also show that a few studies have been conducted on saprotrophic fungi associated with coffee [ 11 ]. Most of the studies focus on pathogens, as pathogenic fungal infections reduce coffee yield and quality, and thus affect farmers’ income and consumers’ health [ 12 , 13 ]. Some research has shown that saprotrophic fungus Phialomyces macrosporus isolated from leaf litter has the potential to be used in the management of coffee halo blight in seedlings [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the likelihood of Fusarium and Aspergillus species producing mycotoxins will increase. Overall, the growth and production potential of Ochratoxin A (OTA) by Aspergillus carbonarius and Aspergillus ochraceus , as well as aflatoxins by Aspergillus flavus , which are more toxic than OTA, may become predominant, leading to an increase in food insecurity surrounding coffee production [ 78 , 79 , 80 ]. Therefore, Arabica and robusta will grow in less suitable climates, increasing plant stress and susceptibility to fungal infection and mycotoxin contamination [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Spontaneous fermented foods may carry traces of mycotoxins. Some researchers have reported aflatoxin and ochratoxin on fermented cacao bean clones [102], arabica and robusta coffee [103], and in the different grains used for the production of traditional fermented beverages [104]. Similarly, the corn and rice used for the production of different types of chicha can carry fungal species that may produce toxic metabolites [105,106].…”
Section: Benefits and Riskmentioning
confidence: 99%
“…The development of mycotoxins has been associated to the length of storage, excessive moisture, and unsanitary handling of certain fermented foods [107]. For instance, a recent study carried out in Brazil detected aflatoxin contamination in 38% of the analyzed cacao samples, while ochratoxin A was detected in 18% of the samples [103]. Similarly, high levels of ochratoxin A were detected in about 25% of the coffee samples [104].…”
Section: Benefits and Riskmentioning
confidence: 99%